Keadaan Kehinaan Dan Kemuliaan Kristus - Deden Andika Saputra; Nafaya Yesilia; Rossan Kurnia; Sarmauli Sarmauli (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
The state of Christ’s humiliation and exaltation represents two essential aspects of Christology, illustrating His journey from incarnation to ascension. Christ’s humiliation includes His humble birth, a life of suffering, and His death on the cross. In contrast, His exaltation encompasses His resurrection, ascension to heaven, and reign as the sovereign King over all creation. This study aims to analyze the theological significance of Christ’s humiliation and exaltation and their relevance to the lives of believers. This research employs a qualitative approach using the library research method, where primary data sources are drawn from biblical texts and Christian theological literature. The findings reveal that Christ’s humiliation is an act of obedience to God the Father and a means of human redemption, while His exaltation serves as evidence of victory over sin and death and the fulfillment of God’s plan of salvation. Furthermore, this study affirms that the relationship between Christ’s humiliation and exaltation has implications for the faith of believers, providing hope for future glory with Christ and calling them to live in obedience and perseverance amid suffering.